2019
DOI: 10.1371/journal.pone.0213197
|View full text |Cite
|
Sign up to set email alerts
|

Introducing chaotic codes for the modulation of code modulated visual evoked potentials (c-VEP) in normal adults for visual fatigue reduction

Abstract: Code modulated Visual Evoked Potentials (c-VEP) based BCI studies usually employ m-sequences as a modulating codes for their broadband spectrum and correlation property. However, subjective fatigue of the presented codes has been a problem. In this study, we introduce chaotic codes containing broadband spectrum and similar correlation property. We examined whether the introduced chaotic codes could be decoded from EEG signals and also compared the subjective fatigue level with m-sequence codes in normal subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…This is in agreement with the findings of our previous study on the comparison between the fatigue levels that simple and rhythmic single-message sinusoidal AM stimuli can cause (Shamsi et al, 2017). It is also in accordance with the results of previous studies on rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual stimuli that reduced the subjective fatigue, and confirms our second hypothesis. In addition, the insignificant and infinitesimal correlation between the fatigue and the psychological state can ensure us that the subjects truly reported the fatigue that was mainly caused by listening to the stimuli, regardless of their psychological status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the findings of our previous study on the comparison between the fatigue levels that simple and rhythmic single-message sinusoidal AM stimuli can cause (Shamsi et al, 2017). It is also in accordance with the results of previous studies on rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual stimuli that reduced the subjective fatigue, and confirms our second hypothesis. In addition, the insignificant and infinitesimal correlation between the fatigue and the psychological state can ensure us that the subjects truly reported the fatigue that was mainly caused by listening to the stimuli, regardless of their psychological status.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, rhythmic stimulation modulates the intrinsic neural oscillatory characteristics (Treder et al, 2014;Herrmann et al, 2016) and facilitates keeping focus (Sato et al, 2019). Interestingly, it was revealed that rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual alongside auditory stimuli (Shamsi et al, 2017) brought about both enough distinguishable EEGs and less subjects' fatigue, compared to simple stimuli. Thus, rhythmic stimuli are one of the promising options for being used in aBCI.…”
Section: Introductionmentioning
confidence: 99%
“…In general, only a few participants rated the flickering sensation during the spelling tasks as exhausting (16% and 5% for the 4-target and 32-target speller) or annoying (14% and 5%). Still, the flickering sensation can be reduced by employing more subtle stimulus patterns 41 , 42 or higher flickering rates 43 , 44 . However, a decrease in performance may be expected as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency-based BCIs may use visual stimuli that are modulated in time according to a sine wave with different temporal frequencies, which also evoke EEG responses at the same frequencies and their harmonics ( Middendorf et al, 2000 ; Müller-Putz et al, 2005 ; Wang et al, 2006 ). Orthogonal visual stimuli in code-based BCIs are generated by random codes such as m -sequences, whereby different shifts of a modulating code have been used to evoke code-modulated VEPs (c-VEPs) ( Nakanishi et al, 2014 ; Riechmann et al, 2016 ; Wei et al, 2016 , 2018 ; Spüler, 2017 ; Liu et al, 2018 ; Shirzhiyan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of visual stimuli with quasi-periodic and chaotic patterns that are closer to natural scenes in BCI applications requires further research. In our previous study, we used chaotic and pseudo-random m -sequence binary codes and found that chaotic codes lead to comparatively less fatigue ( Shirzhiyan et al, 2019 ). In this study, we introduce a new kind of visual stimuli with quasi-periodic and chaotic characteristics to evoke distinct visual potentials in normal subjects for their possible application in VEP-based BCIs.…”
Section: Introductionmentioning
confidence: 99%